1957
DOI: 10.1017/s0022029900008657
|View full text |Cite
|
Sign up to set email alerts
|

663. The relationship between milk secretion and the rate of milking by machine

Abstract: Lactation has two phases: the continuous process of secretion and the mechanism of ejection which occurs only during milking. Because ejection is a transitory phase it is to be expected that within certain limits milk yield will be inversely related to the duration of milking, which, was, in fact, demonstrated many years ago with hand-milked cows(i). With machine milking the situation is different because the forces which the machine applies to the udders of all cows within a herd are the same, and thus the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

1960
1960
1974
1974

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…The results in Table 2 show that the direct relationship between lactation yield and peak flow rate was not close and this result agrees with the findings of Clough and Dodd (1957). There was no simple correlation between lactation yield and milking time.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The results in Table 2 show that the direct relationship between lactation yield and peak flow rate was not close and this result agrees with the findings of Clough and Dodd (1957). There was no simple correlation between lactation yield and milking time.…”
supporting
confidence: 83%
“…The time and rate values used were averages for the three consecutive milkings at which the rate measurements were made. The coefficients of variation in Table 1 show trends similar to those reported by Clough and Dodd (1957) with the highest variability associated with the measures of flow rate and the lowest with milk composition. The mean, minimum and maximum values with the coefficients of variation for each variable are given in Table 1.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…A controversy exists as to the relationship between rate of milking and the total lactation yield. Brumby (1961) demonstrated no genetic correlation between lactation yield and peak flow rate, while other researchers have found rate of milking to be related to lactation yield (Castle and Henderson, 1971;Clough and Dodd, 1957;Dodd and Neave, 1951;Donald, 1960;Johansson and Malven, 1961;Kawanishi et al, 1982;Miller et al, 1976;Rajamannan et al, 1966;Tomaszewski and Legates, 1972). Donald (1960) found that 11% of the variation in yield was removed by holding peak rate constant and concluded that high producing cows tended to be rapid milkers.…”
Section: Milk Flow and Lactation Yieldmentioning
confidence: 98%